Sustainable Development in Fernando de Noronha, Pernambuco, Brazil, according to Tourism Professionals - de Oliveira, Artur Gomes; Tassigny, Mônica Mota; Pompeu, Randal Martins; de Assis, Odéssia Fernanda Gomes (Journal of Tourism, Sustainability and Well-being, 2017)
This study aims to identify how tourism professionals realize sustainable development in Fernando de Noronha, Pernambuco, Brazil, to that end, a questionnaire based on Sen (2010) sustainable development model was applied to a sample of 127 elements and a search in secondary socioeconomic data was performed. The data obtained through the questionnaire were subjected to analysis with the Statistical Package for Social Sciences software to perform an Exploratory Factor Analysis and after, it was made a Confirmatory Factor Analysis using AMOS software. As a result, the socio-economic data indicated the emergence of social and economic problems over time and that the sustainable development model has not been identified, suggesting that, according to the tourism-related professionals, the management model applied to the island does not track the path that leads to sustainability, even when a special attention is given to the preservation of the local environment.